Pembatasan Kebebasan Hak Asasi Manusia dalam Freedom of Speech - Pasaribu, Mia Gisella Kartika (Honeste Vivere, 2025)
Freedom of Speech is one of scope of human rights (HAM). Human rights are a natural right that is inherent in humans and is protected worldwide based on the publication of various human rights instruments by the United Nations (UN). Indonesia as a democratic country participates in full support for freedom of opinion by every citizen who applies the 1945 Constitution article 28E paragraph 3, Law No. 39 of 1999 Article 23 paragraph 2, and Law no. 12 of 2005 concerning Ratification of the International Covenant on Civil and Political Rights (ICCPR). Various normative rules that provide guarantees that freedom will be expressed are in conflict with the normative rules in the ITE Law and the Criminal Code. In essence, inherent human rights must not be limited, but the Siracusa Principles allow action against human rights in certain conditions in each country. The application of legislation has actually been implemented in Article 28J of the 1945 Constitution regarding freedom of rights which are limited to freedom of other rights as well. These human rights restrictions are also included in the Siracusa Principles which are part of the ICCPR. This becomes interesting regarding the extent to which these limitations are legitimate in human rights.